Indicators of Survival and Favorable Functional Outcomes after Decompressive Craniectomy: A Multi-Institutional Retrospective Study. Issue 8 (August 2017) - Khan, Abid D.; Elseth, Anna J.; Head, Brian; Rostas, Jack; Dunn, Julie A.; Schroeppel, Thomas J.; Gonzalez, Richard P.
The role of decompressive craniectomy (DC) for severe traumatic brain injury (STBI) remains controversial. The purpose of this study was to identify factors that are indicators of survival and improved functional outcome in patients who undergo DC for STBI. A retrospective review of STBI patients who underwent DC was performed at four trauma centers during a 45-month period. Data collected included age, gender, mechanism of injury, Injury Severity Score (ISS), admission Glasgow Coma Scale (GCS), time from admission to DC, mortality, and extended Glasgow Outcome Score before discharge. Sixty-nine STBI patients were treated with DC during the study period. A higher initial GCS, lower ISS, and longer time to DC were all statistically significant for improved survival after DC. A younger age, higher initial GCS, and lower ISS were all statistically significant for a favorable functional outcome after DC. Patients with a higher initial GCS and lower ISS are more likely to survive DC and have a favorable functional outcome, whereas a longer time to DC was indicative of improved survival after DC.